THE INFLUENCE OF WORK ETHIC AND WORK ENVIRONMENT ON TEACHER PERFORMANCE WITH PROFESSIONAL COMPETENCE AS AN INTERVENING VARIABLE (Case Study at Al Mamsuriyyah Cikiwul Education Foundation) - Tian Bastian; Slamet Ahmadi (Jurnal Scientia, 2023)
Teachers are the most important factor in education in general because for students teachers are often used as role models, even self-identity figures. Therefore, a teacher is required to perform his competence professionally accompanied by having a high work ethic and good performance supported by a harmonious work environment, this will affect the quality of education. Collaboration between teachers and students can "live" if the teacher is professional. Teachers must have performance that can provide and realize the hopes and desires of all parties, especially the general public who have trusted schools and teachers to nurture students. Based on the above phenomenon, researchers must research the Influence of Work Ethic and Work Environment on Teacher Performance with Professional Competence as an Intervening Variable (Case Study at Al Mamsuriyyah Cikiwul Education Foundation). The study was conducted at the Al Mamsuriyyah Cikiwul Education Foundation, with a research population of 35 teachers, due to population limitations, the samples taken were saturated. For data collection using questionnaire method techniques, and direct observation. And for data analysis using the Smart Partial Least Square (PLS) analysis method version 3.0, for data tests used in this study are reliability tests, validity tests, statistical tests and classical assumption tests.